2010
DOI: 10.1243/09544054jem1762
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of cutting force behaviour considering the effect of cutting edge radius in the micro-scale milling of AISI 1045 steel

Abstract: This paper presents the cutting force behaviour resulting from the effect of cutting edge radius in the micro-scale milling of AISI 1045 steel using tungsten carbide tools. The cutting edge radius of the micro-milling tool is on the order of a few microns or submicrons; hence, the uncut chip thickness reaches the scale of cutting edge radius. Owing to the scaling effect, the cutting force behaviour is different from that in conventional-scale milling. Experiments are conducted with half-immersion milling that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 21 publications
7
24
0
Order By: Relevance
“…By considering the same workpiece material, the results of minimum uncut chip thickness found in this paper match those of Cuba Ramos et al [10], Kang et al [12], Liu et al [8] and Vogler et al [6], even when using different analyzed variables and techniques for measuring or estimating h min .…”
Section: Top View Of the Chip Formationsupporting
confidence: 79%
See 2 more Smart Citations
“…By considering the same workpiece material, the results of minimum uncut chip thickness found in this paper match those of Cuba Ramos et al [10], Kang et al [12], Liu et al [8] and Vogler et al [6], even when using different analyzed variables and techniques for measuring or estimating h min .…”
Section: Top View Of the Chip Formationsupporting
confidence: 79%
“…Kang et al [12] found a similar behaviour of the specific cutting force presented in Fig. 14 when micromilling AISI 1045 steel with a two fluted WC endmill coated with TiNAl (equal to the current).…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…Matsumura and Tamura [21] developed an analytical model to evaluate the effect of the cutter run-out on the cutting force in order to perform the milling operation properly. In addition, the experimental results from Kang et al [22] presented that the effect of cutting edge radius on cutting forces was significant in the micro-scale milling. However, the modelling approaches and techniques developed so far are almost all focused on obtaining the absolute value of cutting forces.…”
Section: Introductionmentioning
confidence: 99%
“…Kang et al [8] investigated the cutting force behavior associated with the effect of cutting edge radius in the micro-scale milling of AISI 1045 steel.…”
Section: Introductionmentioning
confidence: 99%